Local Cost for Global Benefit: The Case of Wind Turbines - Gerhard Kussel; Manuel Frondel; Colin Vance; Stephan Sommer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Given the rapid expansion of wind power capacities in Germany, this paper estimates the effects of wind turbines on house prices using real estate price data from Germany's leading online broker. Employing a hedonic price model whose specification is informed by machine learning techniques, our methodological approach provides insights into the sources of heterogeneity in treatment effects. We estimate an average treatment effect (ATE) of up to -7.1% for houses within a one-kilometer radius of a wind turbine, an effect that fades to zero at a distance of 8 to 9 km. Old houses and those in rural areas are affected the most, while home prices in urban areas are hardly affected. These results highlight that substantial local externalities are associated with wind power plants.
Keywords: Q21; D12; R31; 330; Wind power; hedonic price model